Influence of Pedagogical Conditions over the Process of Creative Self-Realization of Teenagers - Olha Fliarkovska (Pedagogical Discourse, 2014)
This article is devoted to the results of survey research students of secondary schools on the formation of readiness for creative self-realization in the extracurricular educational work. The article focuses on the need to develop creative self-realization of teenagers. It is noted that the set of pedagogical conditions of extracurricular educational activities, provide a positive impact on both the teenager and the teacher on the formation of readiness for creative self-realization of teenagers during extracurricular educational work of an educational institution. Also it stresses on the need for a new objective preconditions for the development of fundamentally new approaches to the adolescent’s preparedness activities, providing him or her the opportunity to more complete and successful creative self-realization. The article states that in the process of preparedness for creative self-realization of teenagers, first performed willingness and ability to action toward creative self-realization there personal involvement in the simulations goals and objectives of their future, while approved by the idea of creative fulfillment.